MAIN ELEMENTS OF THE STATE FINANCIAL POLICY: SCIENTIFIC ANALYSIS - Сторонянська, Ірина; Патицька, Христина; Прокопюк, Александер (Socio-economic relations in the digital society, 2019)
The scientific approaches to the defi nition of the main elements of the state financial policy are considered. It has been revealed that most of the elements of public finance policy are repeated in the approaches of diff erent scholars, but some of them occur only once, demonstrating the uniqueness of scientific views on the structure of the state’s financial policy. It is proved that fiscal and monetary policies are so important that all scholars see all of their elements of financial policy, and all of them are detailed in terms of components such as monetary and credit (monetary policy) and budget and tax (fiscal policy). It is noted that the priority role of scientists is given to budget policy. It was found that all approaches of scientists can be divided into three categories: those that limit the function of tax policy to the tax sector itself; those who pay attention to the functions performed by the tax policy in society, as well as those who consider the tax policy globally — through the prism of infl uence on economic development in general. It is highlighted that domestic science pays considerable attention to the study of investment policy issues. However, it has been determined that these studies are largely theorized, limited in practical use. At the same time, the question of the expediency and implementation of investment policy in the developed economically world countries makes a signifi cant emphasis on the practicality of its implementation. It is generalized that the role of the state in fi scal and monetary spheres is limited by regulatory measures, while researchers have no single directional vision of how they interact. Thus, there is an urgent need for their integrated research in the relationship and in order to develop a unifi ed general vision of the state’s development in this direction. This is necessary for the formation of a springboard for the practical implementation of the state financial policy.